Stability and changes in meaning in life profiles and their impact on mental health among chinese university students: a latent transition analysis - Kwok, Sylvia Y. C. L.; Fang, Siqi; Huang, Bella Meici; Addis Tesfaw, Alebel; Deng, Xi (Frontiers in Psychology, 2025)
BackgroundResearch on meaning in life (MIL) has predominately adopted variable-centered approaches. The few person-centered studies conducted were generally cross-sectional in nature and have failed to address changes in MIL. Furthermore, few studies have explored the stability of and changes in MIL on wellbeing.MethodsWe used latent transition analysis (LTA) to assess the MIL profiles of Chinese university students and to relate their experiences of meaning to their wellbeing. Meaning in Life Questionnaire, Brief Symptom Inventory, and the Mental Health Continuum Short Form were applied. In total, 317 students from five universities in Hong Kong participated in the survey at two time points 9 months apart.ResultsThe LTA identified three distinct profiles among the participants: meaning-oriented, bewildered, and indifferent. The LTA mover–stayer model revealed the relative stability of the students’ MIL profiles over 9 months. Specifically, the indifferent profile group was the most unstable, with a stability of 66.6%, suggesting that a significant portion of students in this group changed profiles. Conversely, the bewildered profile group had the greatest number of movers (64.8%), indicating a higher degree of flux within this group as well. Regarding the adaptive outcomes associated with each profile, results showed that students in the meaning-oriented profile group demonstrated the most adaptive outcomes, evidenced by the highest wellbeing scores and the lowest anxiety and depression scores among all the students.ConclusionThese findings provide insights into MIL profiles and how they change among Chinese university students. We also identified a relatively adaptive profile. Overall, these findings have practical implications and can contribute to advancing research on mental health and meaning.